Prinsip Tanggung Jawab Orangtua Biologis terhadap Anak Di Luar Perkawinan - Rachmadi Usman (Jurnal Konstitusi, 2014)
Every children should get law protection, also children who born from unmarried parent. If it is not, that children be a victim, whereas they was born in holy condition without any mistakes, even they was born as a adultery action. The children who born from unmarried parents often get discrimination and stereotype in society. Because that, toward give protection for children who born from unmarried parents and obligate the father to responsible, Constitutional Court decide provision Article 43 paragraph (1) Act Number 1 of 1974 concerning Marriage is against Constitution of 1945 conditionally, unconstitutional as long as that provision interpretation omit private/civil relation between the man who proved by science and technology and/or other evidence by Law have relationship with their father, and then every children who born from unmarried parents have private/ civil relation not only  with their mother and her family, but also with their father and his family. This decision rise change of meaning and law definition concerning children who born from unmarried parent, include children from adultery couple, as long  as  can  prove by law they have relationship with the man as father also have private/ civil relation with their father and his family. But in other side, Constitutional Court also rise parent (father) biologic principle against children, include children who born from unmarried parent.